The Environmental Education Tourism Development Design Concept in the Citic Seram Energy Limited Area, Maluku Province - Tueka, Fadlia; Basuni, Sambas; Kosmaryandi, Nandi (Media Konservasi, 2024)
The development of environmental education tourism in the area of Citic Seram Energy Limited (CSEL) is a design concept developed from the CSEL Study Tour program, which is an annual Citic Seram Energy Public Relations program sub-field of the Public Education Work Program that has been going on since 2009. This study aims to evaluate CSEL study tour activities as recommendations for developing environmental education tourism in the CSEL area. The method used is a survey method with purposive sampling techniques, namely sampling techniques taken based on certain considerations and objectives. Respondents in this study amounted to 40 people, namely participants in the CSEL study tour in 2013-2019. Data collection techniques use closed-pattern questionnaires with scoring. The processed questionnaire data was then analyzed using IPA (Importance Performance Analysis) to determine the level of performance variables of CSEL study tour activities. The study results show that the perception of study tour participants on the variables of CSEL study tour activities obtained a very high level of importance and satisfaction. This is evidenced by the average importance score obtained, which is 4.68 (very important) and the average satisfaction level score is 4.55 (very satisfied). However, the IPA Diagram shows that the Study Tour and Environmental Conservation Object Variables are in Quadrant I, meaning they are considered important but have satisfaction scores below the expectations of study tour participants. This is a recommendation to increase study tour activities at CSEL in the future.